Empowerment of asnaf Zakat through Zhulqarnain community engagement model - Busari, Saheed Abdullahi (Akademi Zakat (AZKA-PPZ), Pusat Pungutan Zakat (PPZ-MAIWP), 2022)
The increasing quest for sustainable empowerment intervention for the zakat Asnaf has been generating concerns among scholars and policymakers in recent times. One-off zakat assistance for the Asnaf zakat especially the needy and the poor in the contemporary is recommended to alleviate the immediate needs of the recipients, however, there is a dire need in the contemporary time for sustainable empowerment intervention for the Asnaf zakat. This study aims to explore what and how the Zhul-Qarnain community engagement model can be a useful and sustainable approach toward the empowerment of the Asnaf zakat in contemporary Muslim society. The study is qualitative-based research that explores the inductive approach of extracting classical literature and contemporary research work on the importance of empowerment of the asnaf zakat, the significance of the Zhul-Qarnain community engagement model, and its relevance to the empowerment of Asnaf zakat in the modern era. The study will illustrate an interpolative relevance of the Zhul-Qarnain model to solving the challenges of asnaf zakat. The study proposes a sustainable empowerment model for asnaf zakat through the Zhul-Qarnain community engagement model. This study suggests a specific niche for advanced study on the sustainable empowerment model for asnaf zakat.